Heat transfer during reflux condensation of R134a inside a micro-fin tube with different tube inclinations. (February 2017) - Yildiz, S.; Duymaz, G.; Ziegler, F.; Auracher, H.
Highlights: Heat transfer during reflux condensation inside an inclined micro-fin tube is studied. The highest heat transfer rate is obtained at 30° from the horizontal. Heat transfer at 30° inclination is 2.45 times better compared to vertical orientation. Heat transfer in a micro-fin tube is 120% higher than in a plain tube at 30° from the horizontal. Heat transfer is 34% higher in a micro-fin tube than in a rectangular channel at 30° from the horizontal. Abstract: This study presents an experimental investigation of the heat transfer occurring during reflux condensation of refrigerant R134a in an inclined micro-fin tube (0.008 m OD, 0.5 m length). The experiments were carried out at a system pressure of 0.74 MPa and at inclination angles of 30°, 38°, 45°, 60° and 90° from the horizontal. The experiments indicated that the inclination angle has a significant effect on heat transfer during reflux condensation. The maximum reflux heat transfer coefficient was found at 30° inclination angle. At this arrangement, the heat transfer increased by a factor of 2.45 compared to the vertical case. A comparison with previous studies suggests that the heat transfer in a micro-fin tube is 2.2 times better than that in a plain tube, and 1.34 times better than that in a plain rectangular channel both at 30° inclination.